THE IMPORTANCE OF BRANDING FOR BUSINESSES AND ITS IMPACT ON BUILDING CONSUMER LOYALTY - Bilyk , I. I.; Pohyba А. А.; Marhita , M.V. (The actual problems of regional economy development, 2024)
This scientific article delves into the significance of branding for businesses and explores its relevance in the contemporary business landscape. The article traces the origin and evolution of the term "brand" in scholarly literature, underscoring the growing importance of brands for enterprises within the context of competitive rivalry. Brands have transformed into immensely valuable intangible assets for businesses. They exert influence on consumers and foster a dedicated audience capable of distinguishing products or services offered by a particular brand amidst similar offerings in the market. The article introduces a new definition of branding, viewing it as a resource for influencing consumers and enhancing a company's competitiveness. The research highlights that brands are not merely shaped through production but are also constructed in the minds of consumers, establishing an emotional connection between a brand's functionality and how its products are perceived. The primary goal of branding is to craft a brand image that aligns with the needs of the target audience and stands out among comparable products. The article emphasizes the importance of consumer loyalty and brand loyalty as pivotal factors in the development and sustainability of businesses in the contemporary world. It delves into the distinctions between these concepts, elucidating that brand loyalty is grounded in consumers' perception of the brand as a holistic image, which encompasses not only advertising and price but also reputation and interactions with the company. Furthermore, this scholarly work underscores the significance of cultivating consumer loyalty and brand loyalty through an effective branding strategy, encompassing market segmentation, assortment management, consumer education, loyalty programs, and brand positioning. In conclusion, the article asserts that a successful brand demands constant attention and efforts, encompassing both external image and corporate culture. Effective branding within a company can led to numerous competitive advantages, such as reduced advertising costs due to brand recognition, setting higher price points for goods or services, enhancing corporate image, and simplifying the introduction of new products to the market. The results of the study can have practical applications, helping enterprises to develop and implement effective branding strategies to strengthen consumer loyalty and increase their competitiveness.